How Many Brackets Should We Ask for to Derive Adequate Metric Information for Income and Wealth? - Maximilian Longmuir; Markus Grabka (Survey Research Methods)
This paper investigates how the number of brackets and the choice of upper cutoffs in grouped data affect the metric approximation of income and wealth. The literature currently lacks a definition of what should be considered too few brackets or too-low cut-offs. Using German survey data, we show that more than six (eight) brackets and an upper cut-off at the 95th (97th) percentile are sufficient to provide an adequate approximation of the income (wealth) distribution.